Reconfigurable Magnetic Origami Actuators with On‐Board Sensing for Guided Assembly. Issue 25 (9th May 2021) - Ha, Minjeong; Cañón Bermúdez, Gilbert Santiago; Liu, Jessica A.‐C.; Oliveros Mata, Eduardo Sergio; Evans, Benjamin A.; Tracy, Joseph B.; Makarov, Denys
Abstract: Origami utilizes orchestrated transformation of soft 2D structures into complex 3D architectures, mimicking shapes and functions found in nature. In contrast to origami in nature, synthetic origami lacks the ability to monitor the environment and correspondingly adjust its behavior. Here, magnetic origami actuators with capabilities to sense their orientation and displacement as well as detect their own magnetization state and readiness for supervised folding are designed, fabricated, and demonstrated. These origami actuators integrate photothermal heating and magnetic actuation by using composite thin films (≈60 µm thick) of shape‐memory polymers with embedded magnetic NdFeB microparticles. Mechanically compliant magnetic field sensors, known as magnetosensitive electronic skins, are laminated on the surface of the soft actuators. These ultrathin actuators accomplish sequential folding and recovery, with hinge locations programmed on the fly. Endowing mechanically active smart materials with cognition is an important step toward realizing intelligent, stimuli‐responsive structures. Abstract : Magnetic origami actuators equipped with highly compliant magnetic field sensors can monitor their shape and detect their magnetization state, making feedback control and guided assembly possible. These actuators are based on composite films of ferromagnetic microparticles embedded in shape‐memory polymer films. Photothermal heating from light and applied magnetic fields enable on‐demand reconfigurability.